Dr. Stone. 5, Tale for the ages - Inagaki, Riichiro (Shonen Jump manga., 2019)
"One fateful day, all of humanity turned to stone. Many millennia later, Taiju frees himself from the petrification and finds himself surrounded by statues. The situation looks grim--until he runs into his science-loving friend Senku! Together they plan to restart civilization with the power of science!... The Grand Bout Tournament to decide the village chief has begun! Standing in the way of Senku's Kingdom of Science is the powerful warrior Magma, who's facing Kinro in the opening match. Kinro's bad eyesight gives him a decided disadvantage, but thanks to the power of science, a pair of glasses might just be the thing to tip the scales in his favor!"--Provided by publisher.